The crossed and interaction effects of indoor light and thermal factors on human perceptions - Zitong Wang; Yao Fu; Weijun Gao (Developments in the Built Environment, 2024)
Although an interaction between light and thermal physiology has been reported, the combined effects of environmental factors remain unclear. In this study, we experimentally manipulated light and thermal factors to examine the main, crossed and interaction effects on human subjective perception. In this study, we used experimental manipulation of temperature, color temperature, and illuminance levels and repeated measurements to explore the effects on human subjective perceptions in 36 participants.The results showed that temperature significantly influenced visual perception, illuminance and correlated color temperature (CCT) weakly influenced thermal perception. The interaction of temperature and correlated color temperature (CCT) significantly influenced visual perception. In a high-temperature environment, higher CCT enhanced perceived coolness and brightened perceived luminance. However, the interaction of temperature, illuminance and CCT did not influence visual perception or thermal perception. These results seem to confirm that temperature influences human thermal and visual perception in the uncomfortable zone. Along with the actual indoor environment, illuminance and color temperature of the light source at different ambient temperatures should be considered to increase comfort and energy savings.